2015
DOI: 10.1007/s11109-015-9323-7
|View full text |Cite
|
Sign up to set email alerts
|

How Ideology Fuels Affective Polarization

Abstract: Scholars have reached mixed conclusions about the implications of increased political polarization for citizen decision-making. In this paper, we argue that citizens respond to ideological divergence with heightened affective polarization. Using a survey experiment conducted with a nationally representative sample of U.S. citizens, we find that increased ideological differences between political figures produce increasingly polarized affective evaluations, and that these differences are especially large among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
223
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(254 citation statements)
references
References 53 publications
14
223
1
16
Order By: Relevance
“…They found that AP has dramatically surged among the American partisans during the last decades on account of increased hostility between Republicans and Democrats. This study catapulted the affective approach to the forefront of the polarisation debate in the United States, and a number of notable contributions have followed (see Hetherington & Rudolph ; Iyengar & Westwood ; Mason , ; Rogowski & Sutherland ; Lelkes et al. ; Webster & Abramovitz ; Levendusky ; Iyengar & Krupenkin ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They found that AP has dramatically surged among the American partisans during the last decades on account of increased hostility between Republicans and Democrats. This study catapulted the affective approach to the forefront of the polarisation debate in the United States, and a number of notable contributions have followed (see Hetherington & Rudolph ; Iyengar & Westwood ; Mason , ; Rogowski & Sutherland ; Lelkes et al. ; Webster & Abramovitz ; Levendusky ; Iyengar & Krupenkin ).…”
Section: Introductionmentioning
confidence: 91%
“…Thus, we do not know how European countries fare in terms of AP compared to each other and to the United States, not to mention the possible causes and consequences of it. Regarding the foundations of AP and IP‐AP linkage, the current results from the American literature are ambiguous, as some scholars claim that IP has a strong effect on AP (Rogowski & Sutherland ; Webster & Abramovitz ), while others downplay the importance of this relationship (Iyengar et al. ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is little doubt that Democrats and Republicans feel more negatively toward each other now than in the past (Abramowitz & Webster, ; Iyengar, Sood, & Lelkes, ; Iyengar & Westwood, ; Webster & Abramowitz, ), but debate continues over the causes and implications of “affective polarization.” A central point of disagreement concerns the relationship of affect to policy preferences and ideology. Some scholars argue that ideological distance between Democrats and Republicans has increased substantially over the last few decades (Abramowitz, ; Abramowitz & Saunders, ; Bafumi & Shapiro, ), and affective polarization is the result of sharp, principled disagreements over policy (Rogowski & Sutherland, ), especially on size‐of‐government issues related to redistribution and social welfare (Webster & Abramowitz, ).…”
Section: Authoritarianism Affective Polarization and Economic Ideologymentioning
confidence: 99%
“…While scholars agree that partisanship has become stronger, affective partisan polarization more intense, and partisan‐ideological sorting more pervasive, there is less agreement about what underlies these changes in mass partisanship. One popular theory is that the public has become more ideological (e.g., Abramowitz, ; Levendusky, ; Rogowski & Sutherland, ; Webster & Abramowitz, ). This argument states that elite polarization has clarified the ideological brands of the parties and made it easier for the public to construct their political beliefs like ideologues (Converse, ), identifying with the party that best represents their values.…”
Section: A Third Perspective: the Prejudiced Personality Group Centrmentioning
confidence: 99%